Prevalence and risk behaviour for human immunodeficiency virus 1 infection in Marajó Island, Northern Brazil - Vallinoto, Antonio C. R.; Aguiar, Samantha; Sá, Keyla G.; Freitas, Felipe Bonfim; Ferreira, Glenda; Lima, Sandra Souza; Hermes, Renata Bezerra; Machado, Luiz Fernando Almeida; Cayres-Vallinoto, Izaura; Ishak, Marluísa; Ishak, Ricardo (Annals of human biology, 2016)
Background: Human immunodeficiency virus 1 (HIV-1) infection is a global public health problem, but, so far, there is no published information regarding the epidemiology of HIV-1 in Marajó Archipelago (Pará, Brazil). Aim: The present study reports the occurrence of infection by HIV-1 in four municipalities of the Marajó Island, Pará, Brazil. Subjects and methods: A total of 1877 samples were collected from volunteer blood donors (1296 women and 551 men) living in the municipalities of Anajás, Chaves, Portel and São Sebastião da Boa Vista. Information about risk behaviour assessment was obtained from a questionnaire. Plasma samples were tested for the presence of anti-HIV antibodies using serological tests. The infection was confirmed by nucleic acid amplification assays. Results: Twelve samples were seropositive for HIV by ELISA. Western blot analysis showed four positive samples, eight indeterminate patterns and one found to be negative. Molecular analysis revealed three positive samples. Risk factors for HIV-1 infection included absence of condoms during sexual intercourse (41.3%, São Sebastião da Boa Vista), use of illicit drugs (5.8%, Anajás) and early initiation of sexual activities, from 10-15 years (30.7%). Conclusion: Although the study indicates a low HIV-1 prevalence in Marajó Island, some factors may increase the risk for HIV-1 and these include early sexual initiation, unprotected sexual intercourse and the use of illicit drugs.